2000
DOI: 10.1121/1.428344
|View full text |Cite
|
Sign up to set email alerts
|

Radiated noise characteristics of a modern cargo ship

Abstract: Extensive measurements were made of the radiated noise of M/V OVERSEAS HARRIETTE, a bulk cargo ship (length 173 m, displacement 25 515 tons) powered by a direct-drive low-speed diesel engine-a design representative of many modern merchant ships. The radiated noise data show high-level tonal frequencies from the ship's service diesel generator, main engine firing rate, and blade rate harmonics due to propeller cavitation. Radiated noise directionality measurements indicate that the radiation is generally dipole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
176
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(191 citation statements)
references
References 9 publications
11
176
3
1
Order By: Relevance
“…The low-frequency striations during the speed-up are distorted, which are probably due to the complicated source spectra transition between different navigation speeds [36]. However, the overall striation structure is well preserved.…”
Section: Experiments Descriptionmentioning
confidence: 95%
“…The low-frequency striations during the speed-up are distorted, which are probably due to the complicated source spectra transition between different navigation speeds [36]. However, the overall striation structure is well preserved.…”
Section: Experiments Descriptionmentioning
confidence: 95%
“…The average source level for each of these ship types was computed (on the linear scale) based on data contained in McKenna et al (2012) and was found to be 185.6, 181.0 and 185.7 dB re 1 Pa @ 1 m for container ships, oil tankers, and bulk carriers respectively. These data were selected because they are based on relatively new ships and represent values that are lower than those presented in earlier estimates (e.g., Arveson and Vendittis, 2000), thus adding a degree of conservatism to these projections. Finally, the projected fleet-wide source levels were computed by multiplying this average source level on the linear scale by the projected number of ships in each segment of the fleet and then returning the source levels to the decibel scale.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the projected fleet growth is expected to be dominated by larger vessels (Lloyds Register Group, 2013), which are generally noisier (Arveson and Vendittis, 2000). For example, container ships with capacities greater than 7600 twenty-foot equivalent units (TEU) are projected to increase from 20% of the container fleet to approximately 48% by 2030 (Lloyds Register Group, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Small craft with high-speed engines and propellers generally produce higher frequency noise than large vessels (Erbe 2002, Erbe et al 2013. Large vessels, including the cruise ships and tour vessels, generate substantial low frequency noise because of their size and their large, low rpm engines and propellers (Arveson & Vendittis 2000).…”
Section: Introductionmentioning
confidence: 99%